Environmental Stewardship in Islam: Integrating Ethics, Sharia, and Contemporary Da’wah - Mohammed Alhaji Bukar; Umar Alhaji Umar (Walidem Institute and Publishing (WIP), 2025)
Objective: This study examines the role of the global Muslim community (Ummah) in promoting environmental stewardship by integrating Islamic teachings, Sharia principles, and contemporary Da’wah practices. It aims to highlight environmental protection as a religious and ethical responsibility embedded within Islamic faith and communal obligations. Theoretical framework: The study is grounded in core Islamic concepts, particularly tawhid (the oneness of Allah), khilafah (human stewardship of the earth), and amanah (trust), alongside Qur’anic and prophetic teachings that emphasise balance, moderation, and care for nature. These principles provide a normative Sharia-based framework for understanding environmental ethics in Islam. Literature review: Existing literature on Islamic environmental ethics, the socio-religious role of the Ummah, and faith-based environmental movements is reviewed. The discussion highlights how Islamic moral values intersect with sustainability discourse and how Da’wah has been utilised to encourage ethical behaviour, social responsibility, and environmental awareness within Muslim societies. Methods: This study employs qualitative desk research, drawing on secondary sources such as classical Islamic texts, contemporary scholarly works, journal articles, and reports on environmental sustainability and religious engagement. The data are analysed thematically to identify key ethical principles and practical approaches relevant to environmental stewardship. Results: The findings indicate that Islamic teachings offer a comprehensive ethical foundation for environmental protection. Da’wah emerges as a strategic instrument for translating Sharia and ethical principles into practical action, including community education, environmental campaigns, institutional collaboration, and media-based awareness initiatives addressing pollution, resource exploitation, and climate challenges. Implications: The study demonstrates that integrating Da’wah with environmental stewardship can strengthen Muslim engagement in sustainability initiatives and contribute to national and global environmental policies. It also underscores the potential of faith-based approaches to complement scientific and policy-driven environmental efforts. Novelty: This research advances scholarship by explicitly linking Islamic Da’wah with environmental stewardship, presenting a holistic Sharia-based framework that positions the Ummah as an active moral agent in addressing contemporary environmental crises.